2015
DOI: 10.1186/s12890-015-0115-y
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery enlargement in schistosomiasis associated pulmonary arterial hypertension

Abstract: BackgroundSchistosomiasis associated pulmonary arterial hypertension (Sch-PAH) might represent the most prevalent form of PAH worldwide. In Sch-PAH, the presence of aneurismal dilation of the pulmonary artery has been described, although it is still a matter of debate whether on average the pulmonary artery is more enlarged in Sc-PAH than IPAH.MethodsWe retrospectively evaluated patients with IPAH (n = 25) and Sch-PAH (n = 22) who underwent computed tomography pulmonary angiogram and right heart catheterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
(23 reference statements)
0
14
0
4
Order By: Relevance
“…35,36 Furthermore, the clinical and hemodynamic findings of Sch-PAH are also similar to that of IPAH, 37 although with some specific radiological features. 38 Mortality rate seems to be better in Sch-PAH, reaching up to 15% at 3 years, in the absence of a specific therapy. Finally, the response to targeted therapies in Sch-PAH is also similar to other forms of PAH with improvements in hemodynamics and exercise capacity.…”
Section: Schistosomiasismentioning
confidence: 96%
See 1 more Smart Citation
“…35,36 Furthermore, the clinical and hemodynamic findings of Sch-PAH are also similar to that of IPAH, 37 although with some specific radiological features. 38 Mortality rate seems to be better in Sch-PAH, reaching up to 15% at 3 years, in the absence of a specific therapy. Finally, the response to targeted therapies in Sch-PAH is also similar to other forms of PAH with improvements in hemodynamics and exercise capacity.…”
Section: Schistosomiasismentioning
confidence: 96%
“…The initial evaluation of dyspnea may be normal in the early stages of PH or may already evidence abnormalities related to the pulmonary vascular territory. 38 In general, the diagnostic investigation is quite extensive and should encompass all the major mechanisms that culminate in the development of PH. The following constitute the main tests with their most significant findings in PH:…”
Section: Diagnosismentioning
confidence: 99%
“…It was demonstrated that pulmonary artery enlargement is more pronounced in schistosomiasis-induced PAH than an- other form of PAH, suggesting that this is a more distinct feature of schistosomiasis-induced PAH (Figure 3). [43][44][45] Electrocardiography may show right ventricular hypertrophy or strain and right atrial enlargement, and may also reveal a right bundle branch block. Echocardiography may demonstrate right ventricular dilatation, potentially compressing the left ventricle with septal bowing, usually accompanied by right atrial dilation, tricuspid valve regurgitation, and an increased pressure gradient across the tricuspid valve as well as dilatation of the main pulmonary artery.…”
Section: Clinical Presentation Of Schistosomiasis-induced Pahmentioning
confidence: 99%
“…Pulmoner vasküler dilatasyonun pulmoner arter basıncından bağımsız olduğu ileri sürülmüştür. Bu radyolojik bulgunun hastalığın yavaş progresyonuna veya özel bir adaptasyon mekanizmasına bağlı olabileceği düşünülmektedir (11).…”
Section: Kli̇ni̇k Bulgularunclassified